2012
DOI: 10.5539/jas.v4n11p102
|View full text |Cite
|
Sign up to set email alerts
|

Simple Sequence Repeat Molecular Marking Analysis of the Genetic Relationship between Zhaoqing Local Fine Citrus Breeds and Other Citrus and Allied Plants

Abstract: The genetic relationship between Zhaoqing local citrus breeds and other citrus and allied plants was studied using the simple sequence repeat (SSR) molecular marker technique. Among 34 pairs of citrus SSR primers, this study selected 13 primer pairs with high polymorphism to expand 83 bands with 100% polymorphism positive rate. Through cluster analysis, this study effectively differentiated the species, breeds, and even strains of citrus, poncitrus, and atalantia correa. Thus, SSR molecular marker techniques c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…"gonggan" and C. haniana Hort. ex Tseng "Sihuihanggan" have the closest genetic relationship among the local breeds (Ji et al 2012(Ji et al , 2013, consistent with the results of the present study. Some researchers speculate that C. haniana Hort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…"gonggan" and C. haniana Hort. ex Tseng "Sihuihanggan" have the closest genetic relationship among the local breeds (Ji et al 2012(Ji et al , 2013, consistent with the results of the present study. Some researchers speculate that C. haniana Hort.…”
Section: Discussionsupporting
confidence: 92%
“…Samples of three citrus-related genera (Citrus, Poncirus, and Atalantia) were selected in this study. The clustering results showed that the SCoT technique revealed genetic diversity among the tested samples, clustering samples of different genera separately, a result largely consistent with previous studies using RAPD and SSR markers (Ji et al 2011c(Ji et al , 2012. In this study, as the hybrid (P. trifoliata × C. sinensis) of Fructus aurantii and sweet orange, citrange (Poncirus trifoliata (L.) Raf.…”
Section: Discussionsupporting
confidence: 91%